Social determinants of malaria in low- and middle-income countries: a mixed-methods systematic review - Edwinah Atusingwize; Kevin Deane; David Musoke (Malaria Journal)
Abstract Background Malaria remains a leading cause of morbidity and mortality in many low- and middle-income countries (LMICs). Factors outside the health sector, including social determinants, such as economic status remain important drivers of malaria in these settings. However, social determinants of malaria generally remain unaddressed in preventing the disease, with the limited existing evidence overly descriptive and fragmented. Methods A mixed-methods systematic review was conducted to thematically synthesize the current evidence on the social determinants of malaria in LMICs. PubMed, Web of Science, and Scopus were searched to identify English articles on the social determinants of malaria published between January 2013 and December 2023. Search terms such as social determinant, socio-cultural, and socioeconomic factors were used. Articles that did not meaningfully engage with the social determinants were excluded. Results The 39 articles included in the review were mostly cross-sectional and qualitative studies of moderate quality, in general. Findings indicate a range of social determinants of malaria related to the following overarching themes: environmental factors, access to and use of treatment, preventive interventions use, housing, stakeholder influence, livelihoods and economic development, and poverty. The various social determinants influenced malaria in different ways, including limiting access and use of preventive and treatment interventions and increased exposure to mosquitoes. Poverty and gender intersected with other social determinants such as housing and livelihoods. Conclusion Different social determinants of malaria are key drivers of malaria in LMICs. The findings emphasize the need for malaria control efforts to consider social determinants at all levels, including funding, implementation, and evaluation.